Mumbai – Leads Indian Triumph in Global Retail Competition (International Journal of Food and Nutritional Sciences, 2022)
Indian Retail Industry ranking 5th in the world has two sectors viz; organized and unorganized sectors. Since last few years it is observed to be the fastest growing industries in India. The objectives of paper: The main objective behind this research is the analytical thought of huge and enthralling changes occurring in retail sector in the past. With a lot of reference of various articles, reports, newspaper editions and consultations with various academicians it was finally decided to select Mumbai city as base for the research as it has varieties of consumers, any changes takes place in the world it is the first to adopt and is also a financial capital hub of India. The study is a comparison and overview of the Global Retail industry to Mumbai. The report tracks four market segments of countries-viz. US, Australia, China, UK. By understanding these trends a comparison is made with Retail in Mumbai city. On the basis of this comparison a retail picture of Mumbai is given in the study. The study is based on last five years annual trends of retail sector globally.In view of the above fact, the paper outcomes the following objectives: 1. To comprehend the progression of retail sector in India 2. To study the growth trends of Mumbai retail sector 3. To study the growth of retail sector globally as compared to Mumbai.Research Methodology: Sources of information is from journals, books, newspaper, government publications etc. The presented data is in the form of tables and graphs which are analysed at primary and secondary level with form of percent trends and chart.